Active Components and Pharmacological Effects of Cornus officinalis: Literature Review - Gao, Xue; Liu, Yi; An, Zhichao; Ni, Jian (Frontiers in Pharmacology, 2021)
Cornus officinalis Sieb. et Zucc. (Shanzhuyu), a herb and food plant in east Asia, has the properties of tonifying the liver and kidney, and nourishing the essence according to the theory of traditional Chinese medicine (TCM). C. officinalis has been commonly used to treat asthenia diseases, liver and kidney diseases, and reproductive system diseases since ancient times. The objectives of this article were to review the pharmacological effects and phytochemistry of C. officinalis. We conducted a literature review of the pharmacological effects of C. officinalis by different systems and compared the effects with the traditional usages, discussed the research status and potential blanks to be filled. The experimental studies showed that C. officinalis extract and its active components had various pharmacological effects such as anti-oxidation, anti-apoptosis, anti-inflammation, anti-diabetes, anti-osteoporosis, immunoregulation, neuroprotection and cardiovascular protection, but clinical studies are still needed to assess whether the reported pharmacological activities have confirmed efficacy.